The inequality of environmental health awareness among foreign immigrants and local blue-collars at Kuala Lumpur, Malaysia - Kamaludin, Nurul Aina; How, Vivien (Mary Ann Liebert, 2016)
Environmental health awareness programs play an important role in educating people to understand the environmental health conditions of one's working and/or living environment. Even though different environmental health awareness approaches have been conducted among communities for the past decades, the environmental health conditions in developing countries are still worrying. The objective of this study was to assess and understand the environmental health awareness among local and foreign blue-collar workers in Kuala Lumpur, Malaysia. The study recruited 60 foreign immigrants and 60 local blue-collar workers through simple random sampling around Kuala Lumpur. A face-to-face interview was conducted by using a validated questionnaire. Results showed that there were significant differences of environmental health awareness levels among local and foreign blue-collar workers (p < 0.05), except occupational safety and health. The blue-collar workers who live in areas where there are high concentrations of poverty are likely to encounter multiple stressors, including noxious odors, emissions from local industries, illegal dumping, occupational hazards, financial stress, and concerns about crime and safety. This study highlighted the necessity of customizing environmental health awareness by considering differences in background, which may help to enhance the environmental health's perception, practices, and knowledge among the blue-collar populations in this country.